Technical Conditions of Diamond Vaults in Poland - Drobiec, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Diamond vaults represent the greatest achievement of the Gothic architecture. Only about 130 buildings with such vaults have remained to our times, including 30 buildings in Poland. Diamond vaults are less stiff than rib vaults, and consequently more prone to damage. This paper presents technical conditions of diamond vaults in Poland, their typical damage and repair methods.
Keywords: diamond vaults; cell vaults; gothic vaults; technical condition; damage to the vaults; vaults repair